Food processing and breeding strategies for coeliac-safe and healthy wheat products. (August 2018) - Jouanin, Aurélie; Gilissen, Luud J.W.J.; Boyd, Lesley A.; Cockram, James; Leigh, Fiona J.; Wallington, Emma J.; van den Broeck, Hetty C.; van der Meer, Ingrid M.; Schaart, Jan G.; Visser, Richard G.F.; Smulders, Marinus J.M.
Abstract: A strict gluten-free diet is currently the only treatment for the 1–2% of the world population who suffer from coeliac disease (CD). However, due to the presence of wheat and wheat derivatives in many food products, avoiding gluten consumption is difficult. Gluten-free products, made without wheat, barley or rye, typically require the inclusion of numerous additives, resulting in products that are often less healthy than gluten-based equivalents. Here, we present and discuss two broad approaches to decrease wheat gluten immunogenicity for CD patients. The first approach is based on food processing strategies, which aim to remove gliadins or all gluten from edible products. We find that several of the candidate food processing techniques to produce low gluten-immunogenic products from wheat already exist. The second approach focuses on wheat breeding strategies to remove immunogenic epitopes from the gluten proteins, while maintaining their food-processing properties. A combination of breeding strategies, including mutation breeding and possibly genome editing, will be necessary to produce coeliac-safe wheat. Individuals suffering from CD and people genetically susceptible who may develop CD after prolonged gluten consumption would benefit from reduced CD-immunogenic wheat. Although the production of healthy and less CD-toxic wheat varieties and food products will be challenging, increasing global demand may require these issues to be addressed in the near future by food processing and cereal breeding companies. Graphical abstract: Image 1 Highlights: Current gluten-free products are less healthy than gluten-based equivalents. Food processing techniques to produce low gluten-immunogenic products already exist. A combination of breeding strategies will be necessary to produce coeliac-safe wheat. Increasing global demand will require addressing these challenging issues.